Development of a Double Nuclear Gene-Targeting Method by Two-Step Transformation Based on a Newly Established Chloramphenicol-Selection System in the Red Alga Cyanidioschyzon merolae - Fujiwara, Takayuki; Ohnuma, Mio; Kuroiwa, Tsuneyoshi; Ohbayashi, Ryudo; Hirooka, Shunsuke; Miyagishima, Shin-Ya (Frontiers in Plant Science, 2017)
The unicellular red alga Cyanidioschyzon merolae possesses a simple cellular architecture that consists of one mitochondrion, one chloroplast, one peroxisome, one Golgi apparatus and several lysosomes. The nuclear genome content is also simple, with very little genetic redundancy (16.5 Mbp, 4,775 genes). In addition, molecular genetic tools such as gene targeting and inducible gene expression systems have been recently developed. These cytological features and genetic tractability have facilitated various omics analyses. However, only a single transformation selection marker URA has been made available and thus the application of genetic modification has been limited. Here, we report the development of a nuclear targeting method by using chloramphenicol and the chloramphenicol acetyltransferase (CAT) gene. In addition, we found that at least 200-bp homologous arms are required and 500-bp arms are sufficient for a targeted single-copy insertion of the CAT selection marker into the nuclear genome. By means of a combination of the URA and CAT transformation systems, we succeeded in producing a C. merolae strain that expresses HA-cyclin 1 and FLAG-CDKA from the chromosomal CYC1 and CDKA loci, respectively. These methods of multiple nuclear targeting will facilitate genetic manipulation of C. merolae.